SMEs in the Philippine Manufacturing Industry and Globalization: Meeting the Development Challenges - Rafaelita M. Aldaba (Philippine Institute for Development Studies (PIDS), 2008)
In recognition of their substantial contribution to the economy both in terms of number of enterprises and workers, the Philippine government has put in place a number of policies and programs designed specifically to boost SME productivity and competitiveness in the country. However, the performance of SMEs in the last decade has not been vigorous enough to boost the Philippine manufacturing industry. As such, the deepening of high technology industries in terms of the creation of backward linkages has remained weak. While the country's exports of high technology products have grown rapidly, the value added of these exports is very low due to the limited links of large domestic and foreign companies to the domestic economy. Rapid changes in the international trade and the growing complexity of global production system, pose a significant challenge to Filipino SMEs. This paper reviews existing government SME policies as well as recent developments in the manufacturing sector, within the context of the emerging global production network. The paper draws on the findings of a survey interview of SMEs in the automotive, electronics, and garments sectors. The paper highlights the importance of creating a separate government office that would coordinate SME policies and programs to support the integration of SMEs in the global production chain.
Keywords: 330; globalization; small and medium enterprises (SMEs); KMU; Industrie; Internationaler Wettbewerb; Wirtschaftspolitik; Philippinen